2013
DOI: 10.1051/0004-6361/201321184
|View full text |Cite
|
Sign up to set email alerts
|

Towards a theory of extremely intermittent pulsars

Abstract: Aims. We investigate whether there may be one or many companions orbiting at close distance to the light cylinder around the extremely intermittent pulsars PSR B1931+24 and PSR J1841-0500. These pulsars, behaving in a standard way when they are active, also "switch off" for durations of several days, during which their magnetospheric activity is interrupted or reduced. Methods. We constrained our analysis on eight fundamental properties of PSR B1931+24 that summarise the observations. We considered that the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Up to now, research on very low-mass pulsar companions has led to the discovery of five planets (Wolszczan & Frail 1992;Thorsett et al 1993;Bailes et al 2011) and speculations about orbiting asteroids (Cordes & Shannon 2008;Deneva et al 2009;Shannon et al 2013;Mottez et al 2013). These objects raise a moderate interest in the field of planetology: they orbit stars that left the main sequence a long time ago (in a state that the Sun will never reach), they are exposed to the neutron star X-rays that probably prevent life from developing, they are embedded in a relativistic wind, and they are very far away from us.…”
Section: Observational Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, research on very low-mass pulsar companions has led to the discovery of five planets (Wolszczan & Frail 1992;Thorsett et al 1993;Bailes et al 2011) and speculations about orbiting asteroids (Cordes & Shannon 2008;Deneva et al 2009;Shannon et al 2013;Mottez et al 2013). These objects raise a moderate interest in the field of planetology: they orbit stars that left the main sequence a long time ago (in a state that the Sun will never reach), they are exposed to the neutron star X-rays that probably prevent life from developing, they are embedded in a relativistic wind, and they are very far away from us.…”
Section: Observational Testsmentioning
confidence: 99%
“…It is likely that other pulsar planets remain to be discovered. Finally, asteroid belts are likely to exist around pulsars, and they have been invoked by several authors to explain timing irregularities (Shannon et al 2013), anti-glitches (Huang & Geng 2014), or burst intermittency (Cordes & Shannon 2008;Deneva et al 2009;Mottez et al 2013). In this paper we investigate the ability of these bodies immersed in a pulsar wind to produce radio waves.…”
Section: Introductionmentioning
confidence: 97%
“…Akgün et al 2006;Jones 2012) or that there may be some sort of forcing mechanism (e.g. Cordes & Shannon 2008;Rea et al 2008;Mottez et al 2013). Others have suggested that it is a chaotic (Seymour & Lorimer 2013) or Markov (Cordes 2013) process.…”
Section: Introductionmentioning
confidence: 99%
“…A direct electromagnetic interaction between the star and its companions could then be considered. A more detailed analysis of this idea is developed in the companion paper (Mottez et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The idea that PSRB 1931+24 could be orbited by a close swarm of asteroids is discussed in the accompanying paper (Mottez et al 2013). …”
Section: A Companion At Short Distance and A Periastron Precession Wimentioning
confidence: 99%